Pembatalan Perkawinan di Pengadilan Agama: Rekonstruksi Keabsahan Hukum dan Keadilan Sosial Berbasis Pancasila dan Islamic Sociological Jurisprudence Theory - Rifa Ardian Fahreza; Anisah Eka Dewi Saputri; Serlina Atailla Widya Fatihah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
Marriage annulment in Religious Courts has been trapped in rigid legal formalism, giving rise to decision disparities, terminological errors between "null and void" and "voidable", as well as the neglect of the rights of wives and children. This normative legal research with a library research approach aims to reconstruct legal validity and social justice based on Pancasila and the Islamic Sociological Jurisprudence Theory. The results show that the construction of Articles 22-28 of the Marriage Law jo. Articles 70-76 of the Compilation of Islamic Law still leaves a gap between formal legal certainty and substantive justice, reflected in decision disparities between courts and the imposition of mediation excluded by PERMA No. 1 of 2016 which has never succeeded. This study offers a reconstruction with three parameters: marriage validity requires good faith and social consequences; judges need ex officio authority to annul a marriage when tadlīs (identity falsification) is proven; and mediation must be abolished. Pancasila is reconstructed as a rechtsidee (legal ideal) that bridges the formalism of Islamic law and constitutional supremacy, with a recommendation for judicial discretion to provide compensation to wives in good faith based on maqāṣid al-sharī‘ah. This reconstruction is expected to serve as a reference for law enforcers and academics in creating marriage laws that are fair, dignified, and aligned with the values of Indonesian-ness